A retrospective descriptive study of demographics, treatment modalities and outcomes of childhood immune thrombocytopenia at a tertiary hospital in Soweto, South Africa - Mahlalela, Gcebile (University of the Witwatersrand, Johannesburg, 2023)
Background: Primary immune thrombocytopenia (ITP) is an autoimmune mediated disorder and is the most common cause of acquired thrombocytopenia in childhood. Many children will recover spontaneously but treatment may be required to prevent life threatening bleeding. There are controversies regarding treatment options, response rates and predictors of remission in childhood ITP. Objectives: A retrospective review of demographics, treatment modalities and outcomes of children diagnosed with immune thrombocytopenia at a tertiary hospital Methods: Patient records of children between the ages 0-16 years, diagnosed with ITP at Chris Hani Baragwanath Academic Hospital from 01 July 2010 to 30 June 2020 wereretrieved. Data on demographics, clinical presentation, treatments, and outcomes were collected. Outcomes were measured at 1, 3- and 12-months follow-up. Statistica software was used to perform descriptive statistics, and bivariate analyses and logistic regression. Results: 80 files were reviewed but 5 patients were lost to follow-up at 1 month. At 12 months, many patients had been lost to follow-up, with only 35 patients remaining. The mean age at diagnosis was 6.3 years, with 80% of patients less than or equal to 10 years of age. In the study group, 16.3% patients did not receive pharmacologic treatment, and all of these went into remission except one patient lost to follow-up. Younger age, ≤ 10 years was associated with higher rates of remission for all 3 follow-up intervals. Corticosteroids was the most common treatment used and a large proportion of the patients in remission at 1, 3 and 12 months received corticosteroids. The likelihood of remission with a preceding illness in the whole study group was higher, with odds ratios of 2.81, 2.03, and 2.97 at 1, 3, and 12 months respectively. Platelet count, sex and haemoglobin at diagnosis had no significant association with remission. Conclusions: A strategy of watchful waiting can be used in the management of childhood ITP. Younger aged patients with a preceding illness had the highest likelihood of remission, while other predictors showed no significant association with remission. There are no significant differences between our population and the population described in the literature.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Clinical Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023
Keywords: Primary immune thrombocytopenia (ITP); Autoimmune mediated disorder; UCTD; SDG-3: Good health and well-being